Class Master Activity as a Factor of Spiritual Becoming - Martišauskienė, Elvyda (Acta Paedagogica Vilnensia, 1997)
The article discusses the main activities of the class master: the elevation of the value of an individual and the community of entire class; the pursuit of positive relationships with teachers of all subjects; the promotion of positive relations between the teaching staff and schoolchildren; recognition and encouragement of parents’ educational power. So the entire activity of class master is primarily focused on the direct and indirect (through his inspired other educators) interaction with the pupils. On the other hand, this activity conditions the spiritual becoming a class master, it gives meaning to his relationship with reality, especially with other people and himself.